Work-life balance among employees of PERKESO Kuala Lumpur - Idawati, Subari (2018)
This study examined the relationship between four factors; Flexible work arrangement; Job sharing; Leave policy; Wellbeing program towards work-life balance among employees of Perkeso Kuala Lumpur. The study used adapted questionnaire and a total of 234 usable responses were received for a response rate of 90.0 per cent. The responses from the sample are used to test the hypotheses that there is a significant relationship between flexible work arrangement, job sharing, leave policy and wellbeing program towards work-life balance. The results indicated that all four factors mentioned were correlated positively with work-life balance among employees of Perkeso Kuala Lumpur. The findings of this study will help in terms of understanding the work-life balance and the four factors that influenced work-life balance. It was hoped that the findings of this study would add to a larger body of studies of work-life balance and factors that influences it, especially studies among Malaysian organizations.